2016
DOI: 10.1080/2162402x.2015.1098801
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the prognostic value of measures of the tumor inflammatory cell infiltrate and tumor-associated stroma in patients with primary operable colorectal cancer

Abstract: The aim of the present study was to compare the clinical utility of two measures of the inflammatory cell infiltrate -a H&E-based assessment of the generalized inflammatory cell infiltrate (the Klintrup-M€ akinen (KM) grade), and an immunohistochemistry-based assessment of combined CD3C and CD8 C T-cell density (the "Immunoscore"), in conjunction with assessment of the tumor stroma percentage (TSP) in patients undergoing resection of stage I-III colorectal cancer (CRC). Two hundred and forty-six patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 29 publications
4
37
0
1
Order By: Relevance
“…High grade inflammation at the invasive margin was found to be a strong independent prognostic factor for survival in Dukes A and B colorectal carcinomas [62]. The prognostic value of the Klintrup-Mäkinen score has subsequently been validated in independent cohorts [6367]. …”
Section: Tils In Colorectal Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…High grade inflammation at the invasive margin was found to be a strong independent prognostic factor for survival in Dukes A and B colorectal carcinomas [62]. The prognostic value of the Klintrup-Mäkinen score has subsequently been validated in independent cohorts [6367]. …”
Section: Tils In Colorectal Carcinomamentioning
confidence: 99%
“…The relative benefits and limitations of semi-quantitative H&E assessment compared with digital quantitation of IHC stained slides in colorectal carcinoma have begun to be addressed [6567]. The digital image analysis software used by Galon et al was developed in-house and is not publically available for independent validation and comparison with other methodologies [76].…”
Section: Tils In Colorectal Carcinomamentioning
confidence: 99%
“…The prognosis of patients is performed by staging of primary tumor and the involvement of metastases in the lymph nodes and distant organs by standard classification of the Union for International Cancer Control/American Joint Committee on Cancer (UICC/AJCC) classification based upon the tumor-node-metastasis (TNM) (2). However, recent reports in the literature indicated that a considerable heterogeneity of the primary tumor of colon cancer requires a more detailed qualitative analysis, all of its components such as inflammatory response and connective tissue stroma (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…The KM grade, assesses the general local inflammatory infiltrate at the invasive margin using an H&E section, and marks it on a four point score [12]. When Park and co-workers compared the two scores in 246 patients with CRC, the immunoscore stratified patients survival from 93% to 61% (HR 0.66 95% CI 0.56-0.88) and the KM grade from 88% to 66% (HR 0.44 95% CI 0.25-0.76), similar ranges to those seen for TILs [39]. Since the prognostic value of these scores was similar either approach provides a simple, effective method to subtype CMS1 tumours within routine pathology.…”
Section: Phenotypic Characteristics -Immune Infiltrationmentioning
confidence: 82%
“…Parks and coworkers observed that an increase in the tumour stroma as measured by the tumour-stroma percentage (TSP) was a poor prognostic factor for CRC patients (HR 2.46 95% CI 1.56-3.89). TSP stratified 5 year patient survival from 80% (low) to 57% (high) [39]. The TSP measures the percentage of the tumour area infiltrated by stroma, with 50% being a commonly used cut off between low and high.…”
Section: Phenotypic Characteristics -Stromal Invasionmentioning
confidence: 99%